2016
DOI: 10.1002/prot.25097
|View full text |Cite
|
Sign up to set email alerts
|

THz frequency spectrum of protein–solvent interaction energy using a recurrence plot‐based Wiener–Khinchin method

Abstract: The dynamics of a protein and the water surrounding it are coupled via nonbonded energy interactions. This coupling can exhibit a complex, nonlinear, and nonstationary nature. The THz frequency spectrum for this interaction energy characterizes both the vibration spectrum of the water hydrogen bond network, and the frequency range of large amplitude modes of proteins. We use a Recurrence Plot based Wiener-Khinchin method RPWK to calculate this spectrum, and the results are compared to those determined using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…The Fourier spectrum of a time series can be estimated from the RQA measure τ-Recurrence Rate (RR τ ) and is able to identify higher periodic orbits, which a classical spectrum estimation fails to achieve [15]. This technique has already been successfully applied to reveal unstable and stable periodic orbits of various continuous and discrete theoretical dynamical systems [16,17]; to characterize hyperspectral geological data [18], proteinsolvent interaction energy [19], and a phasor measurement unit in electrical power systems [20].…”
Section: Introductionmentioning
confidence: 99%
“…The Fourier spectrum of a time series can be estimated from the RQA measure τ-Recurrence Rate (RR τ ) and is able to identify higher periodic orbits, which a classical spectrum estimation fails to achieve [15]. This technique has already been successfully applied to reveal unstable and stable periodic orbits of various continuous and discrete theoretical dynamical systems [16,17]; to characterize hyperspectral geological data [18], proteinsolvent interaction energy [19], and a phasor measurement unit in electrical power systems [20].…”
Section: Introductionmentioning
confidence: 99%
“…Ge et al (2015) used terahertz absorption spectra to distinguish eight wheat varieties and established a regression model for wheat variety discrimination using the partial least squares method, with a cross-validated correlation coefficient (R 2 ) and cross-validated root mean square error (RMSECV) of 0.985 and 1.162, respectively. Karain (2016) performed terahertz spectroscopy of protein-solvent interaction energy based on the Wiener-Khinchin method and discovered that the spectroscopy spectrum could characterise the spectral range of macromolecular protein mode shapes. Li et al (2017) showed that THz-TDS could be used in qualitative and quantitative research of d-anhydrous glucose, and they provided a reference for rapid glucose detection in fruits, vegetables, foods, and pharmaceuticals using terahertz spectroscopy.…”
Section: Introductionmentioning
confidence: 99%